Effects of nicorandil on the recovery of reflex potentials after spinal cord ischaemia in cats. - Suzuki, T. (1995)
1. The pathophysiological significance of ATP-sensitive K+ (KATP) channels in the central nervous system is not fully understood. In this study the effects of nicorandil (a hybrid vasodilator having a dual mechanism of action as a K+ channel opener and a nitrate) on the recovery of the spinal cord reflex potentials after spinal cord ischaemia were examined and compared with those of pinacidil and nitroprusside in anaesthetized spinal cats. 2. Spinal cord ischaemia was produced by occlusion of the thoracic aorta and the bilateral internal mammary arteries for 10 min. Regional blood flow in the spinal cord was continuously measured with a laser-Doppler flow meter. The monosynaptic (MSR) and polysynaptic reflex (PSR) potentials, elicited by electrical stimulation of the tibial nerve, were recorded from the lumbo-sacral ventral root. The recovery process of spinal reflex potentials was reproducible when the occlusion was repeated twice at an interval of 120 min. 3. Pretreatment with nicorandil (30-100 micrograms kg-1) accelerated the recovery of PSR potentials after spinal cord ischaemia. Such an accelerating effect on the recovery of PSR potentials was also shared by pinacidil (100 micrograms kg-1), another K+ channel opener. In addition, the accelerating effect of nicorandil (100 micrograms kg-1) on the recovery of PSR potentials was abolished by co-administration of glibenclamide (3 mg kg-1), a sulphonylurea KATP channel blocker. Nitroprusside (8 micrograms kg-1min-1) retarded rather than improved the recovery of PSR potentials after spinal cord ischaemia. All of these drugs failed to improve the spinal cord blood flow during ischaemia and reperfusion.(ABSTRACT TRUNCATED AT 250 WORDS)